2012
DOI: 10.1093/cvr/cvs275
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-9 deletion attenuates myocardial fibrosis and diastolic dysfunction in ageing mice

Abstract: MMP-9 deletion attenuates the age-related decline in diastolic function, in part by reducing TGF-β signalling-induced periostin and CTGF expression and increasing MMP-8 expression to regulate myocardial collagen turnover and deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
124
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 154 publications
(139 citation statements)
references
References 38 publications
11
124
0
1
Order By: Relevance
“…Inflammatory cytokines are important contributors to cardiac aging (12,56). To assess whether SPARC mediates cardiac inflammation, we measured the LV expression of inflammatory cytokines and receptors by gene array (Fig.…”
Section: Sparc Expression Increased With Age In LVmentioning
confidence: 99%
“…Inflammatory cytokines are important contributors to cardiac aging (12,56). To assess whether SPARC mediates cardiac inflammation, we measured the LV expression of inflammatory cytokines and receptors by gene array (Fig.…”
Section: Sparc Expression Increased With Age In LVmentioning
confidence: 99%
“…Adult C57BL/6J WT (n ϭ 20, 10 male and 10 female) and Null (n ϭ 21, 10 male and 11 female) mice of 15-18 mo of age were compared. We also compared the 15-18-moold mice to young 6 -9-mo-old WT (n ϭ 12, 6 male and 6 female) and Null (n ϭ 12, 7 male and 5 female) mice that were a randomly selected subgroup from our previous study (7). The previous acquired echocardiography and Doppler data were combined with new gene array, histology, and protein expression results obtained on the tissuebanked samples collected for these mice as well as new samples collected for this study.…”
Section: Micementioning
confidence: 99%
“…We have shown that MMP-9 expression increases with age, concomitant with the development of diastolic dysfunction in wild-type (WT) mice after 18 mo of age (7). This decline in diastolic function was attenuated by MMP-9 deletion in old and senescent mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Металлопротеиназы всегда рассматривались как ферменты деградации межклеточного матрикса. Однако ММР-9 является профиброгенным факто-ром, поскольку обеспечивает процессинг латентной формы TGF-β, переводя его в активную форму, ини-циирующую рост соединительной ткани [8][9][10]. Повышенный уровень синтеза ММP-9 макрофагами в миокарде может указывать на интенсивный фибрил-логенез в зоне ишемии, формирование и экспансию рубца (рис.…”
Section: литератураunclassified